Co-generating knowledge on ecosystem services and the role of new technologies - Buytaert,W; Ochoa,Tocachi B; Hannah,DM; Clark,J; Dewulf,A (Taylor & Francis Group, 2018)
Policy makers are increasingly aware that decision-making in the context of ecosystem services management, and of development, can benefit from collaborative and inclusive approaches to knowledge generation and the design of intervention strategies, such as by providing a more prominent role for indigenous knowledge in decision-making and by using participatory methods for data collection and knowledge generation. In this chapter, we discuss how technologies such as mobile phones, low-cost and robust sensors, and increasingly pervasive remote-sensing satellites and drones can be particularly transformative in the way they facilitate the creation, access and transmission of information about ecosystem services, and support evidence-based decision-making. Furthermore, we discuss how these technologies can be used to promote stakeholder involvement in the knowledge generation process and to make it more inclusive and participatory. While we highlight potential risks related to the use of new technologies, such as exploitation by specific stakeholders to support specific agendas or interests, we identify opportunities for an increasing diversification and tailoring of knowledge creation, moving away from a top-down process dominated by scientists and toward more decentralised, bottom-up and iterative approaches that can have a transformative impact on local ecosystem services management, making it more inclusive, polycentric, evidence-based and robust.